2015
DOI: 10.1597/14-061.1
|View full text |Cite
|
Sign up to set email alerts
|

Is Linear Advancement Related to Relapse in Unilateral Cleft Lip and Palate Orthognathic Surgery?

Abstract: Skeletal and dental relapse was found to be unrelated to the amount of maxillary linear advancement using conventional Le Fort I osteotomies in UCLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Many researchers have studied this relation, with conflicting findings. Some articles have found no association between the two (Proffit et al, 1987;Posnick and Ewing, 1990;Louis et al, 1993;Watts et al, 2015;Bhatia et al, 2016). Bhatia et al showed that maxillary stability after surgery did not depend on the amount of advancement even when the anteroposterior movement was 10 to 22 mm (Bhatia et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have studied this relation, with conflicting findings. Some articles have found no association between the two (Proffit et al, 1987;Posnick and Ewing, 1990;Louis et al, 1993;Watts et al, 2015;Bhatia et al, 2016). Bhatia et al showed that maxillary stability after surgery did not depend on the amount of advancement even when the anteroposterior movement was 10 to 22 mm (Bhatia et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports describing conventional LeFort I osteotomy suggest that an advancement greater than 6 to 10 mm is difficult to achieve with a LeFort I osteotomy because of the potential for speech deterioration and/or the challenges presented by soft-tissue intensity and scarring (Cheung et al, 2006;Alkan et al, 2008;Choi et al, 2012). In contrast, a recent report (Watts et al, 2015) showed that final maxillary advancements of more than 10 mm were achieved successfully using a LeFort I osteotomy. Thus, in the present case, 1 or 2-jaw surgery could have been chosen for treatment.…”
Section: Discussionmentioning
confidence: 95%
“…This is the first study evaluating patients who have undergone more than 10 mm of LeFort I advancement measured postsurgically on the lateral cephalogram. Previous publications have reported larger planned LeFort I advancement of more than !10, but not the actual postsurgical movement (Poole et al, 1986;Houston et al, 1989;Kumar et al, 2006;Watts et al, 2015).…”
Section: Discussionmentioning
confidence: 99%